Assistive Devices to Help Correct Sitting-Posture Based on Posture Analysis Results - Seung-Min Lee; Hyeon-Ju Kim; So-Jeong Ham; Sunhee Kim (Society of Visual Informatics, 2021)
As many people spend a lot of time sitting on a chair, diseases such as turtle neck, straight neck, caused by incorrect posture have been increasing. Preventing these diseases and treating initial symptoms is helpful just by sitting properly. However, when people sit, their postures become disturbed without their knowledge. In this paper, we propose an assistive device in the form of a chair that helps people to sit properly and helps correct their sitting posture. The assistive device is equipped with pressure sensors capable of measuring the distribution of pressure applied to the floor of the chair, and an ultrasonic sensor capable of measuring the distance between the user's back and the chair back. First, an ultrasonic sensor and pressure sensors are used to determine the user's posture, and if the user's posture is not correct, an alarm is sent to the user to help the user to correct the posture by himself. Second, stretching information is provided according to the degree of distribution of pressure measured by the pressure sensors, and pressures are applied to the user's back with press-type cushions to help the user sit in a correct posture. In addition, even when sitting in a chair for a long time, an alarm is triggered to induce a person to rise from the chair. After implementing the system based on Raspberry Pi, each operation was checked. Furthermore, it was confirmed through the experiment participants that the proposed assistive device can help people correct their sitting posture.